RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN MELON (Cucumis melo L.) TERHADAP KOMBINASI BIODEGRADABLE SUPER ABSORBENT POLYMER DENGAN PUPUK MAJEMUK NPK DI TANAH MISKIN HARA - Suryawaty ,; Rida Wijaya (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
AbstractThis study was aimed to determine the response of vegetative growth and yield of Mask Melon (Cucumis melo L.) grown on poor soil affected by the application of Biodegradable Super Absorbent Polymer combined with compound fertilizer (NPK 16-16-16). The study was carried out in Marelan Research Centre, PT. Sentana Adidaya Pratama (PT. SADP), Marelan Street-Pasar V (Bumi Permai Housing Complex), Medan with the altitude of ± 4 meter above sea level. The experimental design used was a non factorial Randomized Complete The parameters measured were plant height (cm), initial flowering time (day), harvesting time (day), fruit weight (g), fruit diameter (cm) and number of fruits produced per plot (fruit). Based on the results data analysis on the respond of vegetative growth and yield of Mask Melon (Cucumis melo L.) affected by various treatments combination of Biodegradable Super Absorbent Polymer and compound fertilizer (NPK 16-16-16) in poor nutrient soil, among treatments tested did not give any significant effect on the parameters measured such as plant height, initial flowering time, harvesting time, fruit weight, fruit diameter and number of fruits produced per plotKeywords: Mask Melon, BSAP and NPK